An ergonomic comparison of rowing machine designs: possible implications for safety - Bernstein, I. A.; Webber, O.; Woledge, R. (British Journal of Sports Medicine, 2002)
Objectives: Ergometer training is a common cause of injuries in rowers. A randomised crossover study comparing two power head designs was carried out to examine ergonomic risk factors. Methods: Six elite male rowers undertook 20 minute fatiguing rowing pieces with both fixed and floating power heads. A CODA MPX infrared telemetric motion analysis detector and the ergometer's interface were used to measure displacement, force, work performed, and power output. Results: There was no significant difference in the total work performed, power per stroke, or metabolic load between the two ergometer designs. Fatigue was shown by a mean (SEM) fall of 9.7 (0.79) W/stroke (95% confidence interval (CI) 8.0 to 11.5) between minutes 8-10 and minutes 16-18 (p<0.001). The stroke length was 53 (13) mm (95% CI 18 to 89) longer with the fixed power head (p<0.02). With fatigue, the stroke with the fixed power head lengthened at the "catch" (beginning of the stroke) by 19.5 mm (p<0.01) and shortened at the finish of the stroke by 7.2 mm (p<0.05). No significant changes in stroke length were seen with the floating power head. The mean force per stroke was 12.1% (95% CI 3.0 to 21.2) (27.3 (8.0) N) higher with the power head fixed versus floating (p<0.02). Conclusions: It is postulated that longer stroke lengths and greater forces are risk factors for soft tissue injuries. Further research into whether floating power head rowing ergometers are associated with lower injury rates than fixed power head designs is now needed. Br J Sports Med 2002;36:108-112